2016
DOI: 10.5897/ajar2016.11482
|View full text |Cite
|
Sign up to set email alerts
|

Growth and production of a Japanese cucumber crop under pulse irrigation

Abstract: Water is the most important production factor in agriculture, since even small restrictions to the water supply can result in decreased productivity. Due to climatic reasons, water supply is limited in many parts of the world, resulting in a need to develop techniques that increase the water use efficiency. Pulse irrigation consists of the application of an irrigation depth, relative to the actual irrigation needed, split throughout the day. The objective of this study was to verify the effects of pulse irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Almeida, Lima and Pereira (2015) observed water saving of 25% with the use of pulse drip irrigation as compared with continuous drip irrigation in lettuce cultivation. For Maller et al (2016), pulse drip irrigation has the potential to save about half of the irrigation water in the greenhouse compared with conventional drip irrigation. WUE as a function of water salinity obtained an estimated value of 7.55 kg m -3 with local-supply water (0.3 dS m -1 ), decreasing by 0.54 kg m -3 (7.01%) per unit increase in ECw, reaching a value of 5.28 kg m -3 at the highest level of water salinity (4.5 dS m -1 ), totaling a relative decrease of 30.1% when comparing the two salinity levels (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Almeida, Lima and Pereira (2015) observed water saving of 25% with the use of pulse drip irrigation as compared with continuous drip irrigation in lettuce cultivation. For Maller et al (2016), pulse drip irrigation has the potential to save about half of the irrigation water in the greenhouse compared with conventional drip irrigation. WUE as a function of water salinity obtained an estimated value of 7.55 kg m -3 with local-supply water (0.3 dS m -1 ), decreasing by 0.54 kg m -3 (7.01%) per unit increase in ECw, reaching a value of 5.28 kg m -3 at the highest level of water salinity (4.5 dS m -1 ), totaling a relative decrease of 30.1% when comparing the two salinity levels (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…65, No. SI:13 (2022) (Maller et al, 2016;Abdelraouf et al, 2020c;El-Shawadfy et al, 2020;El-Shafie et al, 2021), lettuce (Almeida et al, 2015, green beans (Almeida et al, 2018), almond (Phogat et al, 2013) and eggplant (Arriero et al, 2020). These studies found that pulse irrigation outperformed continuous irrigation in terms of water savings, enhanced yield, and the quality of the product.…”
Section: -Introductionmentioning
confidence: 99%